Physical and Combustion Properties of Briquettes Produced from Composite Materials of Daniela Oliveri, Gmelina Arborea and Bambara Nut Shells in Benue State, Nigeria - T., Tembe, E.; O., Ekhuemelo, D.; W., Asue, M. (International Journal of Pure Agricultural Advances, 2018)
Composite biomass materials from Daniela oliveri, Gmelina arborea and Bambara nut shells were used to produce briquettes in binary combination of Daniela oliveri with bambara nut shells and Gmelina arborea with bambara nut shells in a ratio of 1:1. Bambara nut shells were first ground into fine particles and sundried for 7 days, cassava starch was used as binder in the proportion of 25% starch to 100g of composite material. Briquettes were produced using a cylindrical mould at a pressure of 2 kNm-2 and used to determine the compressed (density at 0 minute after processing)) and relaxed densities (density at 30 minute, 1 hour, 24 hours and 7 days after processing), Shattered index and combustion properties (% moisture content, % fixed carbon, % volatile matter, % ash content and specific heat of combustion). The result showed a gradual reduction in compressed and relaxed densities as drying time increased from 0 minute to 7 days because of a reduction in the relaxation. Composite briquettes from Gmelina arborea with bambara nut shells recorded a higher relaxed density of 0.59 g/cm3 in 7 days and a significantly higher shatter resistance and weight loss of 99.93 % and 0.07% respectively. Composite briquettes from Daniela oliveri with bambara nut shells produced a higher significant effect of 11388.8 Kcal/kg compared with Daniela oliveri with bambara nut shells with Specific Heat of Combustion of 10944.0 Kcal/kg. Briquettes produced from composite materials of Daniela oliveri with bambara nut shells and Gmelina arborea with bambara nut shells therefore suitable for used as alternative cooking fuels in rural and sub-urban communities in Nigeria.